2020
DOI: 10.1200/jop.19.00450
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Adolescents’ and Young Adults’ Attitudes Toward Participation in Cancer Clinical Trials

Abstract: PURPOSE: Participation in cancer clinical trials (CCTs) for adolescents and young adults (AYAs) remains the lowest of any patient group with cancer. Little is known about the personal barriers to AYA accrual. The aim of this study was to explore AYA attitudes that influence CCT participation. METHODS: A mixed-methods approach was used. AYAs and non-AYAs (≥ 40 years) completed the Cancer Treatment subscale of the Attitudes Toward Cancer Trials Scales and 9 supplementary questions formed from interview analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Namely, AYAs indicated that they had difficulties finding information tailored to their experience as a AYA, desired age-specific recommendations, and were concerned about the trustworthiness of internet sites. In addition, our study found that older adults searched more often for clinical trials online compared to AYAs, which is in line with the underrepresentation of AYAs participating in clinical trials [ 17 ].…”
Section: Discussionsupporting
confidence: 63%
“…Namely, AYAs indicated that they had difficulties finding information tailored to their experience as a AYA, desired age-specific recommendations, and were concerned about the trustworthiness of internet sites. In addition, our study found that older adults searched more often for clinical trials online compared to AYAs, which is in line with the underrepresentation of AYAs participating in clinical trials [ 17 ].…”
Section: Discussionsupporting
confidence: 63%
“…52 Despite plentiful studies of barriers and facilitators to clinical trial enrollment among AYAs, few interventions or system-level changes (eg, simplifying enrollment) have addressed such barriers. [52][53][54][55][56][57][58][59][60][61][62][63] A metaanalysis suggests that moderate improvements have been made over the past decade in AYA clinical trial availability. 63 However, new collaborations may have the potential to further increase AYA enrollment.…”
Section: Aya Barriers and Facilitators To Clinical Trial Accessmentioning
confidence: 99%
“…We defined two categories of independent variables: 1) patient sociodemographic and disease characteristics, and 2) most responsible physician (MRP) characteristics. Sociodemographic characteristics included sex (male/female), age at diagnosis (defined as <40, 40–64, ≥65), 19,20 primary language (English, language other than English, or unknown), federal electoral district (FED) of the patients’ primary residences (based on 6‐digit postal code), 21 distance (km) of primary residence from the cancer center, community‐level marginalization, and presence of a primary care provider (PCP). The 2013 FED distribution, which divides the province of Ontario into 121 geographical areas with similar population sizes, was used as the ecologic unit of analysis to control for region.…”
Section: Methodsmentioning
confidence: 99%